Step
*
1
1
1
of Lemma
es-first-at-since-iff
1. es : EO@i'
2. i : Id@i
3. e : E@i
4. [P] : {e:E| loc(e) = i ∈ Id}  ─→ ℙ
5. [R] : {e:E| loc(e) = i ∈ Id}  ─→ ℙ
6. ∀e:E. Dec(R[e]) supposing loc(e) = i ∈ Id@i
7. loc(e) = i ∈ Id@i
8. P[e]@i
9. ¬R[e]@i
10. ∀e':E. ((e' <loc e) 
⇒ P[e'] 
⇒ (∃e'':E. (e' ≤loc e''  ∧ (e'' <loc e) ∧ R[e''])))@i
11. e'' : E@i
12. (e'' <loc e)@i
13. P[e'']@i
14. e''@0 : E
15. e'' ≤loc e''@0 
16. (e''@0 <loc e)
17. R[e''@0]
18. e' : E
19. e' = e ∈ E
20. R[e']
21. ∀e'':E. ((e' <loc e'') 
⇒ e'' ≤loc e  
⇒ (¬R[e'']))
⊢ (e' <loc e)
BY
{ ContradictionViaCongruence `reference_environment` }
1
1. es : EO@i'
2. i : Id@i
3. e : E@i
4. [P] : {e:E| loc(e) = i ∈ Id}  ─→ ℙ
5. [R] : {e:E| loc(e) = i ∈ Id}  ─→ ℙ
6. ∀e:E. Dec(R[e]) supposing loc(e) = i ∈ Id@i
7. loc(e) = i ∈ Id@i
8. P[e]@i
9. ∀e':E. ((e' <loc e) 
⇒ P[e'] 
⇒ (∃e'':E. (e' ≤loc e''  ∧ (e'' <loc e) ∧ R[e''])))@i
10. e'' : E@i
11. (e'' <loc e)@i
12. P[e'']@i
13. e''@0 : E
14. e'' ≤loc e''@0 
15. (e''@0 <loc e)
16. R[e''@0]
17. e' : E
18. e' = e ∈ E
19. R[e']
20. ∀e'':E. ((e' <loc e'') 
⇒ e'' ≤loc e  
⇒ (¬R[e'']))
⊢ R[e]
Latex:
1.  es  :  EO@i'
2.  i  :  Id@i
3.  e  :  E@i
4.  [P]  :  \{e:E|  loc(e)  =  i\}    {}\mrightarrow{}  \mBbbP{}
5.  [R]  :  \{e:E|  loc(e)  =  i\}    {}\mrightarrow{}  \mBbbP{}
6.  \mforall{}e:E.  Dec(R[e])  supposing  loc(e)  =  i@i
7.  loc(e)  =  i@i
8.  P[e]@i
9.  \mneg{}R[e]@i
10.  \mforall{}e':E.  ((e'  <loc  e)  {}\mRightarrow{}  P[e']  {}\mRightarrow{}  (\mexists{}e'':E.  (e'  \mleq{}loc  e''    \mwedge{}  (e''  <loc  e)  \mwedge{}  R[e''])))@i
11.  e''  :  E@i
12.  (e''  <loc  e)@i
13.  P[e'']@i
14.  e''@0  :  E
15.  e''  \mleq{}loc  e''@0 
16.  (e''@0  <loc  e)
17.  R[e''@0]
18.  e'  :  E
19.  e'  =  e
20.  R[e']
21.  \mforall{}e'':E.  ((e'  <loc  e'')  {}\mRightarrow{}  e''  \mleq{}loc  e    {}\mRightarrow{}  (\mneg{}R[e'']))
\mvdash{}  (e'  <loc  e)
By
ContradictionViaCongruence  `reference\_environment`
Home
Index